0D-2D Quantum Dot Metal Dichalcogenide Nanocomposite Photocatalyst Achieves Efficient Hydrogen Generation - Liu, Xiao-Yuan (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.